Identification and Structural Characterization of an Unknown Trace Degradation Impurity in Cabazitaxel Injection by LC-DAD-SPE-NMR/MS - LIU Hongbing; LIU Huili; LUO Liting; SUN Lijuan; CHEN Lei (Chinese Journal of Magnetic Resonance)
In this work, the hyphenated liquid chromatography-diode array detector-solid phase extraction-nuclear magnetic resonance/mass spectrometry (LC-DAD-SPE-NMR/MS) technique is employed to characterize a novel degradation impurity with an approximate content of 0.3%~0.4% in cabazitaxel injection. In LC analysis, the impurity is co-eluted with tween-80, an important excipient contained in cabazitaxel injection, which poses a great challenge for high-purity degradation impurity isolation and further structure elucidation. Based on LC-DAD-SPE-NMR/MS hyphenation, automatic SPE is performed to trap and concentrate the impurity, and extensive NMR analysis was performed to characterize the structure of the impurity. In the 1H NMR spectrum, partial peaks of the impurity are overlaid with co-eluted tween-80. To navigate the complexity, 1H-1H, 1H-13C correlations, 1H and 13C chemical shifts are extracted from the interfering peaks of tween-80 based on extensive analysis of 2D NMR spectra. Finally, the structure of the impurity is elucidated to be a cabazitaxel isomer with a rearranged taxane skeleton. The elucidation is completed in less than 48 h, showcasing a successful application of LC-DAD-SPE-NMR/MS hyphenation in determining the structure of an unknown trace impurity in pharmaceutical drugs, which evidences its capability and application prospects in the pharmaceutical industry.